2020
DOI: 10.3389/fneur.2020.00713
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability Parameters During Psychogenic Non-epileptic Seizures: Comparison Between Patients With Pure PNES and Comorbid Epilepsy

Abstract: Significance: A few studies examined HRV alterations in PNES, reporting high sympathetic tone (although less evident than in epileptic seizures). Our data suggest a sympathetic overdrive before and during PNES followed by a post-PNES increase in vagal tone. A sympathovagal imbalance was more evident in pPNES as compared to PNES/ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Beat detection and correction routines [47] were reimplemented in-house to extract the inter-beat interval series (RR) which was interpolated using third degree splines. In accordance with previous papers [48,49], after making the signal analytic through Hilbert transformation, for each RR series, a time-frequency representation was estimated by computing its Smoothed Pseudo-Wigner-Ville distribution using the time-frequency toolbox documented in [50]. The instantaneous spectral power of the heart high-frequency (HF) band in the interval [0.15-0.4 Hz], which is a proxy for the parasympathetic activity, was then obtained through frequency-averaging and successively convolved with a standard double gamma Haemodynamic response function (α 1 = 6, α 2 = 16, β 1 = 1, β 2 = 2, c = 0.17) [51].…”
Section: (Ii) Brain-heart Interactionssupporting
confidence: 93%
“…Beat detection and correction routines [47] were reimplemented in-house to extract the inter-beat interval series (RR) which was interpolated using third degree splines. In accordance with previous papers [48,49], after making the signal analytic through Hilbert transformation, for each RR series, a time-frequency representation was estimated by computing its Smoothed Pseudo-Wigner-Ville distribution using the time-frequency toolbox documented in [50]. The instantaneous spectral power of the heart high-frequency (HF) band in the interval [0.15-0.4 Hz], which is a proxy for the parasympathetic activity, was then obtained through frequency-averaging and successively convolved with a standard double gamma Haemodynamic response function (α 1 = 6, α 2 = 16, β 1 = 1, β 2 = 2, c = 0.17) [51].…”
Section: (Ii) Brain-heart Interactionssupporting
confidence: 93%
“…Besides epilepsy, a substantial number of the patients admitted to EMUs present with PNES, and a smaller group displays an association of both pathologies (35,36). It is shown that PNES patients manifest functional, anatomical, and autonomic brain changes compared with healthy subjects and epilepsy patients without PNES (37)(38)(39)(40). On the other hand, it is suggested that a wide range of psychopathologies may be the basis of PNES and that their treatment could improve clinical outcomes, avoiding the perpetuation of ongoing psychogenic seizures (35).…”
Section: Discussionmentioning
confidence: 99%
“…Autonomic changes described in patients with PNES are starting to show possible contributors such as heart rate variability during PNES. 12 Prospective studies in this population may be able to answer these questions in the future.…”
Section: Commentarymentioning
confidence: 98%